Antidiabetic activity of Curculigo latifolia extracts in vitro and in vivo studies - Ishak, Nur Akmal (2014)
Curculigo latifolia (C. latifolia) plant grows wildly in tropical Asia especially in Malaysia. C. latifolia fruit has 9000 times the sweetness of sucrose. The sweet taste of C. latifolia fruit is due to a protein known as curculin. This indicates that C.latifolia plant has the potential to be used as an alternative low-calorie sweetener for diabetic patients. Besides, natural phenolic compounds contained in C. latifolia which posses antioxidant activity can also be used to prevent and treat diabetes. In the present study, antidiabetic properties of C. latifolia in cell lines (in vitro) and in diabetic-induced rats were determined. Different parts of C. latifolia plant (fruit, root and leaf) were extracted using distilled water and then were freeze dried into powder. Total phenolic content and free radicals scavenging activity of C. latifolia fruit, root and leaf extracts were determined. C. latifolia fruit and root extracts exhibited higher scavenging free radicals activity (1.0 mg/ml) and followed by leaves extract (1.2 mg/ml). Besides, C.latifolia fruit extracts showed high phenolic content (95 mg GAE/100 g extract) and followed by roots (90 mg GAE/100 g extract), leaf in hot (100oC) water (83 mg GAE/100 g extract) and leaf in normal (at room temperature) water (74 mg GAE/100 g extract). In in vitro study, different concentrations (0.01, 0.025, 0.05, 0.1, 0.5, 1.0 and 3 mg/ml) of C. latifolia fruit, root and leaf extracts were screened for cytotoxicity effect towards BRIN- BD11 pancreatic, L6 myotubes and 3T3 adipocytes cells using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H tetrazolium) (MTS) assay. Results showed that C. latifolia fruit and root extracts did not cause toxicity towards BRIN-BD11 pancreatic, L6 myotubes and 3T3 adipocytes cells. However, C. latifolia leaf extracts at 2.3 mg/ml caused 50% BRIN BD11 cell death. Furthermore, the effect of C. latifolia as potential antidiabetic agent was evaluated by measuring: (1) insulin secretion by BRIN-BD11 pancreatic cells (2) radio labelled 2-Deoxy-D-glucose (2DOG) uptake by 3T3 adipocyte and L6 myotubes and (3) adiponectin secretion by 3T3 adipocytes. Results from insulin assay showed that C. latifolia roots extract increased 40% of insulin over basal secretion followed by C. latifolia fruits extract (35%) in BRIN BD11 pancreatic cells. Whereas, leaves extract did not show significant increment. Meanwhile, results from 2DOG uptake activity showed that C. latifolia fruits extract significantly increased (p<0.05) 2DOG activity with insulin present up to 13 fold (at 0.05 mg/ml) in 3T3 adipocytes and 16 fold (at 0.1 mg/ml) in L6 myotubes. However, C. latifolia roots extract at 0.05 mg/ml significantly increased (p<0.05) 2DOG activity without insulin presence up to 2 fold in 3T3 adipocytes and L6 myotubes. Present study also indicates that with insulin presence, C. latifolia leaves extract at 0.1 mg/ml increased 21 fold of adiponectin secretion. However without insulin presence, C. latifolia roots extract increased 6 fold adiponectin secretion. The effectiveness of C. latifolia fruit and root extracts in increasing insulin secretion, 2DOG uptake and adiponectin secretion in vitro study were then confirmed by study on diabetes-induced rats. Combination of C. latifolia fruit and root (1:1) v/v used to treat the diabetes-induced rats. Diabetes rats were developed by feeding high fat diet (HFD) which contained 56.9% calorie contributed by fat and low dose (40 mg/kg bw) STZ injection. After acclimation period, rats were fed high fat diet for 30 days and were then injected with 40 mg/kg bw of STZ via intravenous (iv) injection at the tail. Rats were divided into seven groups; 1) normal rats, 2) obese rats (only fed with HFD), 3) diabetic rats (induced with HFD and low dose STZ), 4) diabetic rats treated with 50 mg/kg b.w of C. latifolia fruit:root (1:1) extracts, 5) diabetic rats treated with 100 mg/kg b.w of C. latifolia fruit:root extracts,6) diabetic rats treated with 200 mg/kg b.w of C. latifolia fruit:root extracts and 7) diabetic rats treated with 10 mg/kg b.w of glibenclamide. Treatment period was 30 days. Before and after treatments, biochemical parameters such as glucose, insulin,adiponectin, total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), triglycerides (TG), urea, creatinine, alanine aminotransferase (ALT) and plasma γ-glutamyltransferase (GGT) were measured. Results showed that 200 mg/kg b.w of C. latifolia fruit:root extracts reduced significantly (p<0.05) 65% plasma glucose and 49% of total cholesterol level. Besides, with the same concentration it also increased 12% insulin and 41% of adiponectin levels in plasma. Furthermore, 50, 100 and 200 mg/kg b.w of C. latifolia fruit:root extracts showed that urea, creatinine, ALT and GGT levels in diabetic-induced rats were reduced towards normalcy after 30 days of treatment. The regulatory effects of C. latifolia fruit:root extracts on genes involved in glucose and lipid metabolisms were further studied. Ten genes; IGF-1, IRS-1, GLUT4,PPARγ, PPARα, AdipoR1, AdipoR2, leptin, lipoprotein lipase and lipase were analyzed using GenomeLab GeXP Genetic Analysis System. Results showed that treatment with 200 mg/kg b.w of C. latifolia fruit:root extracts effectively improved glucose metabolism in diabetic-induced rats due to increase expression of insulin signaling receptor (IRS-1 (4 fold) and IGF-1 (4 fold)), glucose transporter (GLUT 4 (2 fold)) and peroxisome proliferator-activated receptor (PPARγ (8 fold) and PPARα (2 fold)). It also showed to improve lipid metabolism by increasing the expression of adiponectin receptor (AdipoR1 (5 fold) and AdipoR2 (4 fold)), leptin (5 fold), lipase (3 fold) and lipoprotein lipase (2 fold). Based on the current findings, it can be concluded that C. latifolia fruit:root extracts exhibit antidiabetic properties due to higher total phenolic content and its ability to scavenge free radicals. It effectively improved glucose and lipid metabolisms in diabetic-induced rats by increased IGF-1, IRS-1, GLUT4, PPARγ, PPARα,AdipoR1, AdipoR2, leptin, lipoprotein lipase and lipase genes regulation. All of the results demonstrate potential use of C. latifolia in diabetic therapy.